Litter decomposition and nutrient dynamics of selected multipurpose trees in homesteads - Sheeba Rebecca Isaac (Department of Agronomy, College of Agriculture, 2001)
An investigation was undertaken in three homegardens at Kalliyur Panchayat, Thiruvananthapuram District during the period 1998 - 1999, to analyse the structure, quantify the litter production and to assess the decomposition characteristics of leaf litter of commonly grown multipurpose trees. The six tree species selected for the study were mango, jack, cashew, ailanthus, wild jack and mahogany. Decomposition studies were carried out in the homegardens, beneath the respective tree species canopy and in an exposed area, which served as the control plot. The standard litter bag technique was adopted for the purpose. The changes in the soil properties associated with the decomposition were monitored at both sites The homegardens studied represented a multi-storied tree based cropping system with coconut palms being the most dominant species. The other tree species common to the three homegardens were mango, jack, cashew, wild jack, morinda and mahogany. The farmers effectively utilized the interspaces and theymostly relied on tuber, fodder and spice crops for income. There was no definite pattern of arrangement but the cropping intensities worked out for the homegardens were high. The amount of litter accumulated in the homegardens annually by the different tree components varied with the species, its density and prevailing climatic conditions. Homegarden I recorded the highest amount of litter addition followed by the homegardens 11 and III studied. The litter added